MANAJEMEN WAKAF BERBASIS KELOMPOK , SOLUSI PEMBERDAYAAAN PETANI DAN KETAHANAN PANGAN - Bagus Pratama Susanto (LP2M IAI Miftahul Ulum Pamekasan, 2020)
Indonesia is known as the largest agrarian country in the world, but it is ironic to see Indonesian farmers who are still far from well-fulfilled economic, educational and health welfare. So that they are trapped in poverty continuously. The government as the party that has an important role has not done much in resolving this problem. As a result, the actions taken by the government have no effect on the agricultural sector in Indonesia. The potential for waqf, especially land in Indonesia, is so great. This can be maximized by the government and the private sector. Agricultural subsidies, which in the future will be reduced and eliminated, will be quite a difficult problem for the Indonesian agricultural sector. Land waqf and cash waqf can be used as an alternative to this subsidy. Even more than that, with the concept of agricultural empowerment that uses waqf funds as funding it will make empowerment sustainable and raise the income of farmers. In addition, the group system or joint responsibility allows farmers to develop the values ​​of togetherness, trust, care and empathy for others both in terms of humanity and financial obligations. So that national food security can continue to increase. Keywords: group based, land waqf, food self-sufficiency